2022
DOI: 10.3389/fcell.2022.810474
|View full text |Cite
|
Sign up to set email alerts
|

Thy-1 (CD90), Integrins and Syndecan 4 are Key Regulators of Skin Wound Healing

Abstract: Acute skin wound healing is a multistage process consisting of a plethora of tightly regulated signaling events in specialized cells. The Thy-1 (CD90) glycoprotein interacts with integrins and the heparan sulfate proteoglycan syndecan 4, generating a trimolecular complex that triggers bi-directional signaling to regulate diverse aspects of the wound healing process. These proteins can act either as ligands or receptors, and they are critical for the successful progression of wound healing. The expression of Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 267 publications
(315 reference statements)
0
11
0
Order By: Relevance
“…Wound healing is a complex multistage process involving many molecular interactions and signaling pathways that permit successful repair of the skin. Thy-1 has been considered a protein of interest in this process because its upregulation during the inflammatory stage has been associated with angiogenesis [ 16 , 17 ]. Here, we demonstrated that the lack of Thy-1 in mice retards the wound healing process and impairs re-epithelialization associated with decreased blood perfusion during the healing process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wound healing is a complex multistage process involving many molecular interactions and signaling pathways that permit successful repair of the skin. Thy-1 has been considered a protein of interest in this process because its upregulation during the inflammatory stage has been associated with angiogenesis [ 16 , 17 ]. Here, we demonstrated that the lack of Thy-1 in mice retards the wound healing process and impairs re-epithelialization associated with decreased blood perfusion during the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…The contraction would be different if the lesion were more extensive and if the location were in a place where the skin is looser (medium dorsum) or tighter (between the ears). Therefore, cells are affected by different mechanical forces, which are known to affect the responses of the Thy-1/integrin/syndecan-4 complex [ 17 ]. Unfortunately, the paper by Sedov et al did not discuss the differences between their findings and those previously reported by Lee and co-workers [ 18 ], which demonstrated the opposite effect caused by Thy-1 deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of fibroblast-DC interaction, the Thy-1–integrin interaction might also play an important role in DC migration, since integrins are recognized players of cell migration. In this skin inflammatory model, IL-6 was recognized for the first time as a cytokine capable of inducing DC production of MMP9 and thus, as an important regulator of DC migration [see recent review on this topic in ( Perez, Leyton et al, 2022 )].…”
Section: Thy-1 Directly Binds Integrins In Transmentioning
confidence: 99%